Winter warming effects on soil nitrate leaching under cover crops: A field study using high-frequency weighing lysimeters - Lapierre, Jared; Machado, Pedro Vitor Ferrari; Debruyn, Zachary; Brown, Shannon E.; Jordan, Sean; Berg, Aaron; Biswas, Asim; Henry, Hugh A. L.; Wagner-Riddle, Claudia (Frontiers in Environmental Science, 2022)
Leaching of nitrate (NO3−)—a reactive nitrogen form with impacts on ecosystem health—increases during the non-growing season (NGS) of agricultural soils under cold climates. Cover crops are effective at reducing NGS NO3− leaching, but this benefit may be altered with less snow cover inducing more soil freezing under warmer winters. Our objective was to quantify the effect of winter warming on NO3− leaching from cover crops for a loamy sand (LS) and a silt loam (SIL) soil. This research was conducted over 2 years in Ontario, Canada, using 18 high-precision weighing lysimeters designed to study ecosystem services from agricultural soils. Infra-red heaters were used to simulate warming in lysimeters under a wheat-corn-soybean rotation planted with a cover crop mixture with (+H) and without heating (-H). Nitrate leaching determination used NO3− concentration at 90 cm (discrete sampling) and high temporal resolution drainage volume measurements. Data were analyzed for fall, overwinter, spring-thaw, post-planting, and total period (i.e., November 1 to June 30 of 2017/2018 and 2018/2019). Warming significantly affected soil temperature and soil water content—an effect that was similar for both years. As expected, experimental units under + H presented warmer soils at 5 and 10 cm, along with higher soil water content in liquid form than –H lysimeters, which translated into higher drainage values for + H than –H, especially during the overwinter period. NO3− concentrations at 90 cm were only affected by winter heating for the LS soil. The drainage and NO3− concentrations exhibited high spatial variation, which likely reduced the sensitivity to detect significant differences. Thus, although absolute differences in NO3− leaching between LS vs. SIL and +H (LS) vs. –H (LS) were large, only a trend occurred for higher leaching in LS in 2018/2019. Our research demonstrated that soil heating can influence overwinter drainage (for LS and SIL soils) and NO3− concentration at 90 cm in the LS soil—important NO3− leaching controlling factors. However, contrary to our initial hypothesis, the heating regime adopted in our study did not promote colder soils during the winter. We suggest different heating regimes such as intermittent heating to simulate extreme weather freeze/thaw events as a future research topic.